The time-course changes in postural control variability between neck pain and asymptomatic dental students - Manuel Barbosa Almeida; Marion Moreira; José Moreira; João R. Vaz; Paula Moleirinho-Alves; Raúl Oliveira (Scientific Reports)
Abstract Changes in postural control associated with clinical practice or specific conditions such as the presence of neck pain remain unexplored in dental students. Therefore, this study aimed to explore the time-course changes in postural control complexity among dental students enrolled in clinical practice, comparing those with and without neck pain. We used an online Nordic Musculoskeletal Questionnaire for group allocation and center of pressure (CoP) oscillations with a tri-axial Bertec force plate. Baseline data were acquired from dental students with neck pain (NP) (n = 21) and asymptomatic in a control group (n = 23), before starting their clinical practice, and assessments were repeated after their first semester. CoP fluctuations were determined through the calculation of sample entropy. Both groups had similar postural control at baseline, but asymptomatic students exhibited more irregular CoP AP (p = 0.013) and ML (p = 0.015) oscillations, while students with neck pain showed a more rigid pattern (p = 0.004) in the AP direction at the endpoint. Our results showed that dental students’ postural control complexity decreased during the first semester of clinical practice. Over time, asymptomatic students exhibited more random postural control patterns, while students with neck pain demonstrated more rigid postural control during upright stance, indicating that postural control complexity differs between students with and without neck pain when exposed to clinical training.